Las estrategias metodológicas que utilizan los docentes del área de ciencias sociales en el proceso de enseñanza-aprendizaje con los niños y niñas de quinto, sexto y séptimo grados del subnivel básica media de educación general básica de la escuela “Filomena Rojas Ocampo” barrio Bolonia, parroquia Sucre, ciudad y provincia de Loja. Año lectivo 2012-2013 - Pizarro Duran, Teresa de Jesús (2014)
This research work refers to: Methodological strategies used by teachers in the area of Social Sciences in the teaching-learning process with children in fifth, sixth and seventh grades of General Basic Education School Red Philomena Ocampo neighborhood Bologna, Parroquia Sucre, city and province of Loja. 2012-2013 school year. It was proposed as a central objective, the establishment of the relationship between the applications of the methodological strategies in the teaching - learning process in the area of Social Sciences. Books, specialized encyclopedias, as well as computer, electronic memory, CDs, bon A4 paper and photocopies: the main materials as employed. It was necessary to use methods such as scientific method; the descriptive method, the analytical method - synthetic and theoretical - deductive, which allowed the development of the process in each of its phases. Structured interviews, the survey and the interview guide and questionnaire were the techniques and tools applied to the Principal, teachers and students of the institution, respectively, allowed obtaining the relevant information. The research universe consisted of 87 people. Among the main results emerged that teachers apply if, in an acceptable manner, the approaches in the teaching-learning area of Social Sciences. The conclusion was reached that asserts that the application of the approaches facilitates teaching and student learning in the area of Social Sciences. The main recommendation emphasizes that the Director manages training to update teachers in the specific field of the approaches to ensure an efficient process of teaching - learning